(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article examines the characteristics of the Russian-language media in Uzbekistan from the period when Uzbekistan became an independent state. “The Fourth Estate” is another name for the media, since the media consider and exercise control over other areas of various organizations. They also prepare the ground for the correct decision to be made in internal and external political processes by the leaders of any state; they pay great attention to the shortcomings of the governing bodies themselves. At the same time, state power, in order to convey its diplomacy to the vast masses and mobilize them for creative participation, also uses the media.